Deep Learning Based Skin Cancer Diagnosis - Arik, Alper; Golcuk, Mesut; Karsligil, Elif Mine (IEEE, 2017)
Melanoma is the deadliest form of skin cancer. Early diagnosis has vital importance in the healing of the disease. As human expertise is in limited, automated systems capable of identifying disease could save lives, reduce unnecessary intervention and costs. Toward this goal, in this paper we propose a system that uses recent deep learning methods that are capable of classitication of skin lesions for melanoma detection.
Keywords: Deep learning; machine learning; skin cancer diagnosis; melanoma detection; convolutional neural networks; Acoustics; Computer Science; Engineering; Telecommunications